Strip show : performances of gender and desire - Liepe-Levinson, Katherine, 1953- (Gender in performance., 2002)
Katherine Liepe-Levinson has spent three years researching heterosexual female and male striptease in North America: this is the first full length theoretically informed study of striptease.